PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MENGGUNAKAN APLIKASI GOODNOTE - Arwansyah; Muhammad Akmansyah; Sovia Mas Ayu; Afifuddin Ahmad Robbani (Jurnal Pendidikan Islam, 2024)
Education has its origins in the term 'Learning'. Learning refers to relatively permanent transformations in behavior or behavioral potential that arise from reinforced experience or practice. Teaching materials in PAI learning at SMP IT Ar-Raihan are contextual using technology based on the Goodnote application, because the large influence of media (such as television, newspapers, magazines, internet and radio) on society indirectly influences the cognitive condition of students in The meaning of words for them is that it is easier to describe real (factual) events or things compared to imagining something abstract. So PAI learning using the Goodnote application has a significant impact on the learning outcomes carried out in class. This research uses the library research method or literature review based on several books and journals which are then collected into research conclusions. The research results show that there are several positive impact points obtained from PAI learning using the Goodnote application, including; a) using the Goodnote application in PAI learning helps students make digital summary notes of material. So that students no longer need to use paper notebooks which have the risk of being torn, wet, or even damaged due to student negligence. b) using the Goodnote application in PAI learning helps educators explain PAI material practically and systematically. Apart from that, it also makes it easier for educators to note various important points in each chapter or sub-chapter of material. C) using the Goodnote application in PAI learning helps to introduce technology in PAI learning so that educators and students are not technologically challenged and appear more modern and sophisticated.